Spectroscopic investigations of Dy3+‐doped tungstate–tellurite glasses for solid‐state lighting applications. (8th June 2022) - Vikas,; Jayasimhadri, Mula; Haranath, Divi
Abstract: A series of Dy 3+ ‐activated lithium–tungstate–tellurite (LTT) glasses have been synthesized employing a conventional melt quenching procedure. The structural and luminescent features of LTT glasses were examined in detail to reveal their feasibility in solid‐state lighting (SSL) applications. Various physical parameters such as density, molar volume, and other parameters were evaluated. A broad hump showed in the X‐ray diffraction profile affirms the non‐crystalline or amorphous behavior of the as‐prepared LTT glasses. The absorption spectrum exhibits several bands between the 400 and 1800 nm range, which confirms that the transitions initiate from the lowest energy state ( 6 H15/2 ) to numerous excited states. Photoluminescence (PL) spectra reveal three significant peaks centered at 481 (blue), 575 (yellow), and 664 nm (red) related to Dy 3+ ions under 388 nm excitation. The chromaticity coordinates of LTT glasses were situated in the white light region and nearest to the standard white light (0.33, 0.33). The decay profile shows the biexponential behavior of the prepared LTT ( x  = 0.1, 1.0, and 2.0 mol%) glasses. Temperature‐dependent PL spectra show appreciable thermal constancy of the prepared LTT glasses having a high value of activation energy. The previous results indicate that Dy 3+ ‐doped tungstate–tellurite glasses are potential luminescent materials to utilize in SSL applications, especially for white light‐emitting diodes.